Assessing the reliability to detect cerebral hypometabolism in probable Alzheimer's disease and amnestic mild cognitive impairment - Wu, Xia; Chen, Kewei; Yao, Li; Ayutyanont, Napatkamon; Langbaum, Jessica B.S.; Fleisher, Adam; Reschke, Cole; Lee, Wendy; Liu, Xiaofen; Alexander, Gene E.; Bandy, Dan; Foster, Norman L.; et al. (Journal of neuroscience methods, 2010)
▶ Measure hypometabolism reliability for FDG-PET using Bootstrap resampling. ▶ Discuss this reliability with the hypometabolism consistency over multi-datasets. ▶ Characterize this reliability relation to the parametric type-I error. ▶ Propose its use for longitudinal study and for multiple comparison correction. Fluorodeoxyglucose positron emission tomography (FDG-PET) studies report characteristic patterns of cerebral hypometabolism in probable Alzheimer's disease (pAD) and amnestic mild cognitive impairment (aMCI). This study aims to characterize the consistency of regional hypometabolism in pAD and aMCI patients enrolled in the AD neuroimaging initiative (ADNI) using statistical parametric mapping (SPM) and bootstrap resampling, and to compare bootstrap-based reliability index to the commonly used type-I error approach with or without correction for multiple comparisons. Batched SPM5 was run for each of 1000 bootstrap iterations to compare FDG-PET images from 74 pAD and 142 aMCI patients, respectively, to 82 normal controls. Maps of the hypometabolic voxels detected for at least a specific percentage of times over the 1000 runs were examined and compared to an overlap of the hypometabolic maps obtained from 3 randomly partitioned independent sub-datasets. The results from the bootstrap derived reliability of regional hypometabolism in the overall data set were similar to that observed in each of the three non-overlapping sub-sets using family-wise error. Strong but non-linear association was found between the bootstrap-based reliability index and the type-I error. For threshold p=0.0005, pAD was associated with extensive hypometabolic voxels in the posterior cingulate/precuneus and parietotemporal regions with reliability between 90% and 100%. Bootstrap analysis provides an alternative to the parametric family-wise error approach used to examine consistency of hypometabolic brain voxels in pAD and aMCI patients. These results provide a foundation for the use of bootstrap analysis characterize statistical ROIs or search regions in both cross-sectional and longitudinal FDG-PET studies. This approach offers promise in the early detection and tracking of AD, the evaluation of AD-modifying treatments, and other biologically or clinical important measurements using brain images and voxel-based data analysis techniques.